Estimation of Gene Frequencies in Clinical Research - Vijayalakshmi, N.; P.Sekhar, Dr.; G.Mokesh Rayalu, Dr. (International Journal of Engineering and Technology, 2018)
Biometrics is a branch of statistics in which various mathematical and statistical techniques can be applied to biological research problems. These are two main areas of specialization of Biometry namely, Bioassays and Quantitative Genetics. Genetics concerns with Heredity and variation. Quantitative Genetics is concerned with the inheritances of quantitative differences between individuals.The essence of Quantitative Genetics is to estimate the genetic parameters such as Gene frequencies, segregation Ratios, Recombination of Genes and so on. Among them, the estimation of Gene Frequencies in the population is an important one. The proportion or percentage of genes in the population is called gene Frequency. In the present research articles, the ABO blood group system of man has been described by discussing the multiple alleles; genotypes, Frequencies and phenotypes of blood groups. The various estimation methods for estimating gene frequencies have gene presents in the present study.Â